1993
DOI: 10.1007/bf01743168
|View full text |Cite
|
Sign up to set email alerts
|

An improved approximation for stress constraints in plate structures

Abstract: An improved approximation for stresses (and strains) in plate structures is presented. This approximation is highly accurate because it is based on approximations of the element forces, which are more invariant than the element stresses and strains, and because it captures the nonlinearity in the stress recovery calculations. Both sizing and shape design problems are used as examples to show the increased accuracy and iobustness of this approximation function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Vanderplaats [12,13] has shown that, approximating the internal forces first as a linear function of the design variables, is more accurate than approximating the stress constraints directly. In this approach, the linear approximations are used to calculate the internal forces from which the stresses and hence the failure constraint(s) (e.g., von Mises stress) may be calculated.…”
Section: Successive Convex Approximation Methodsmentioning
confidence: 99%
“…Vanderplaats [12,13] has shown that, approximating the internal forces first as a linear function of the design variables, is more accurate than approximating the stress constraints directly. In this approach, the linear approximations are used to calculate the internal forces from which the stresses and hence the failure constraint(s) (e.g., von Mises stress) may be calculated.…”
Section: Successive Convex Approximation Methodsmentioning
confidence: 99%
“…FEAP command consists of "TANG,,1" for linear analysis or a loop of same command for nonlinear analysis. In case one desires employing the adjoint sensitivity, then first the adjoint vector is calculated for a performance function using (6). For this purpose, a user macro is constructed to calculate sensitivity performance to response −( / D).…”
Section: Feap Implementationmentioning
confidence: 99%
“…The material has = 10×10 6 psi (69 GPa) and ] = 0.3. A numerical design is also calculated in [6] with fewer optimization iterations by exploiting improved Journal of Optimization 7 3 3.608 3.566 Tip deflection in. 0.500 0.495 approximation techniques.…”
Section: Compliance Objective and Distributed Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the optimal section properties are found, the stress is calculated based on the new properties, and a new approximation in terms of the physical properties is made. This is repeated until the stress converges (Vanderplaats and Thomas 1993;Vanderplaats and Kodiyalam 1990).…”
Section: Introductionmentioning
confidence: 99%